PENGARUH PELATIHAN KETERAMPILAN KOMUNIKASI TERHADAP KECERDASAN EMOSI - Wildan . (LPPM STAI La Tansa Mashiro, 2013)
The aim of this research is to determine the effect of communication skill training on emotional intelligence at student of Al Hafidz Qur’an boarding schools in Palembang. The population includes all the student of Al Hafidz Qur’an boarding schools, in the school year 2011-2012. The random samples consist of 30 students who had a low score in emotional intelligence. The samples were divided into two groups of 15 students as the experimental groups were given training in communication skills for 6 sessions, while 15 students as a control group did not provide training in communication skills. The results showed that communication skills training significantly improves of emotional intelligence.